Aboutness in Fiction: Methodological Perspectives for Knowledge Organization - Ernesto de Moraes, Joao Batista [UNESP] (Ergon-verlag Gmbh, 2012)
The subject analysis of narrative texts of fiction is complex; the methodological model of identification of concepts as elaborated for scientific texts is not applicable to fiction. It is proposed here that theoretical and methodological use of the Generative Trajectory of Meaning postulated by Greimas may contribute to the identification of aboutness in narrative texts of fiction.